Pendidikan Pajak Syariah Al-Kharaj Dalam Meningkatkan Wawasan Ekonomi Syariah di Kalangan Mahasiswa STIE Ganesha Jakarta - Hendra Candra; Joned C. Saksana; M. Arief Noor; Haria Saputri; Cinta Rahmi; Nabilla Akmas; Isnaini Muharrifah; Nabila Soraya; Nurhayati Nurhayati; Wahyuni Wulandari; Ambar Syafirlah Azzara; Yasir Rumuar; Muhammad Nur Hidayat; Rosliana Rosliana; Indah Dwi Prafitasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The sharia economy offers a different approach from conventional economics, prioritizing the principles of justice, transparency, and sustainability. In the sharia economic system, there are various instruments that must be understood in depth by the actors. One of these instruments is sharia tax or known as Al-Kharaj. Al-Kharaj is a type of tax levied on land conquered by Muslims and administered by the government. This concept not only contains financial aspects but also has high social values and justice. This community service activity uses a lecture and discussion method aimed at STIE Ganesha Semester 4 Regular A. Management S1 students A. This activity is prepared for approximately 3 (three) months which includes the preparation, planning and implementation stages. The implementation of the activity was carried out for 1 (one) day, where the PKM team consisted of 4 (four) STIE Ganesha dsen and 8 (eight) students, where the lecturer was responsible for compiling the material and giving lectures, while students assisted in logistics and documentation to ensure that the activity ran smoothly and effectively. With a clear and interactive presentation, the lecture session succeeded in providing participants with a deep understanding of Al-Kharaj sharia tax and with an interactive and collaborative atmosphere, the discussion session succeeded in deepening the participants' understanding and giving them the opportunity to apply the concepts they have learned in practical situations.